Polyphenol content and antioxidant capacity in ethanolic exytacts of organic and conventional fruits (Red apple, lady finger banana and papaya) - Oo, May Kyaw; Darnis, Deny Susanti (2014)
Due to the importance, the natural polyphenol studies are being carried out around the world. This study also aimed to determine the total phenolic content (TPC), total flavonoid contetnt (TFC) and antioxidant capacity (DPPH) of three organic and conventional fruits pairs (red apple (Malus domestica), lady finger banana (Musa acuminata) and papaya (Carica papaya). The fruits were extracted by maceration in absolute ethanol. Then TPC of fruit extracts were determine by using Folin-Ciocalteau method with quercetin as standard. Aluminium chloride assay was be used to determine TFC with quercetin as standard. For antioxidant capacity, % inhibition and IC 50 of the extracts were calculated using DPPH radical method along with trolox standard. For every test, the absorbances were measured by using UV/VIS spectrophotometer at certain wavelenght. This researc was carried out in triplicates starting from sample collection. As a result, it is found out that there is no difference in TPC and TFC values between apple pair. TPC and TFC values between banana pair also show no difference while the value of conventional papaya are significantly higher than those of organic papaya. For DPPH test result, organic apple and organic papaya have higher antioxidant capacity than those of conventional ones while there is no difference in antioxidant capacity between banana pair. It is also found out that there is no relationship between TPC and their antioxidant capacity